2020
DOI: 10.26444/aaem/128236
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and job satisfaction of healthcare workers in Slovenian nursing homes in rural areas during the COVID-19 pandemic

Abstract: Introduction and objective. Since there is no study on burnout and job satisfaction in Slovenian nursing homes during the COVID-19 pandemic, this study aims to analyse job satisfaction and burnout levels of healthcare professionals working in Slovenian nursing homes in rural areas during the COVID-19 pandemic, and make a comparison with the results of the same services in 2013. Materials and method. The study is based on a cross-organisational and descriptive quantitative study conducted in spring 2013 (n = 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 18 publications
9
77
0
7
Order By: Relevance
“…Regarding the satisfaction of PHCWs during the first wave of COVID-19, most of the respondents were not satisfied with their capacity for work, means of transport and money to meet their daily needs. Our findings agreed with studies in the past on satisfaction of healthcare workers which revealed there was a low level of satisfaction among these workers [19,20]. This could be as a result of the lockdown and the harassment of the people including the healthcare workers though to a lesser extent by the security operatives.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the satisfaction of PHCWs during the first wave of COVID-19, most of the respondents were not satisfied with their capacity for work, means of transport and money to meet their daily needs. Our findings agreed with studies in the past on satisfaction of healthcare workers which revealed there was a low level of satisfaction among these workers [19,20]. This could be as a result of the lockdown and the harassment of the people including the healthcare workers though to a lesser extent by the security operatives.…”
Section: Discussionsupporting
confidence: 91%
“…Of the 16 studies included, 2 were conducted in the USA [ 32 , 33 ], 3 in the United Kingdom [ 34 , 35 , 36 ], 1 in Australia [ 37 ], 1 in Germany [ 38 ], 1 in Canada [ 39 ], 1 in Sweden [ 40 ], 1 in Spain [ 41 ], 3 in the Netherlands [ 42 , 43 , 44 ], 1 in Slovenia [ 45 ], 1 in Malaysia [ 46 ], and 1 in several Latin American (Peru, Mexico) and European (Spain and Italy) countries [ 47 ]. Fifteen were in English and only one was in Spanish [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to methodology, the 16 studies included 5 mixed methods studies [ 38 , 39 , 42 , 43 , 45 ], 7 qualitative studies [ 32 , 34 , 35 , 37 , 41 , 46 , 47 ], 1 short report [ 36 ], 1 rapid scoping review [ 44 ], and 2 studies using another approach such as a letter or report containing a first-hand testimony [ 33 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In turn, the need for positive staff to self-isolate contributed to a 'perfect storm' of understaffing at many facilities [28]. Reports suggested that there was a greater probability of having COVID-19 resident infections in nursing homes where registered nurse levels were under the recommended minimum [20,29,30]. To emphasise the significance of this problem, a study suggested that a 20-min increase in registered staffing was associated with a 22% reduction in COVID-19 cases and 26% fewer COVID-19 deaths [31].…”
Section: Staffing-related Factorsmentioning
confidence: 99%